2016
DOI: 10.1111/iju.13163
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative urinary incontinence exacerbates nocturia‐specific quality of life after robot‐assisted radical prostatectomy

Abstract: Although the number of nocturia episodes was not significantly different between the continent and incontinent patients after surgery, the Nocturia Quality of Life questionnaire score was significantly worse in incontinent patients. In these patients, other than the number of nocturia episodes, psychological stress might worsen the Nocturia Quality of Life questionnaire score. Therefore, prevention of post-prostatectomy incontinence might be important to avoid aggravating the Nocturia Quality of Life questionn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 27 publications
(63 reference statements)
0
19
0
Order By: Relevance
“…According to the results of multivariate analysis, the aggravating factors of the Japanese version of the nocturia QOL score revealed nocturnal frequency and urinary incontinence . Nocturnal frequency was the same in the continence and incontinence groups; however, the Japanese version of the nocturia QOL score was worse in the incontinence group, which might be because of psychological stress . Mean nocturnal frequency before RP was almost the same at 1 year after RP; however, evaluation of each patient showed that nocturia of 20–30% patients improved, whereas that of the other 20–30% of patients worsened after RP …”
mentioning
confidence: 99%
See 3 more Smart Citations
“…According to the results of multivariate analysis, the aggravating factors of the Japanese version of the nocturia QOL score revealed nocturnal frequency and urinary incontinence . Nocturnal frequency was the same in the continence and incontinence groups; however, the Japanese version of the nocturia QOL score was worse in the incontinence group, which might be because of psychological stress . Mean nocturnal frequency before RP was almost the same at 1 year after RP; however, evaluation of each patient showed that nocturia of 20–30% patients improved, whereas that of the other 20–30% of patients worsened after RP …”
mentioning
confidence: 99%
“…After RP, anatomical changes in the pelvis cause functional changes in the lower urinary tract. Furthermore, in regard to chronological changes in nocturnal frequencies, the nocturia worsened at 3 months after RP, and it returned to almost the same pre‐RP level at 1 year after RP . Subjective QOL was evaluated using a validated Japanese version of the nocturia QOL questionnaire, and objective urinary frequency and urine volume were evaluated using the 24‐h frequency–volume chart .…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…In the article by Haga et al ., the authors address the issue of nocturia‐specific quality of life (QoL), in relation to post robot‐assisted laparoscopic radical prostatectomy (RARP) incontinence . Nocturia, i.e.…”
mentioning
confidence: 99%